FORMULATION AND EVALUATION OF MASLINIC ACID LOADED TRANSDERMAL PATCHES - CHOUDHORY, NEHA; KAUR, TARANJIT; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2021)
Objective: To develop and evaluate Transdermal patch of Maslinic acid for Transdermal drug delivery. The current study is to develop Transdermal drug delivery system. Methods: Suitable method such as Solvent Casting Technique of Film Casting Technique are used for preparation of Transdermal patch. Results: The prepared Transdermal patches were transparent, smooth, uniform and flexible. The method adopted for the preparation of the system was found satisfactory. Conclusion: Various formulations were developed by using hydrophilic and hydrophobic polymers like HPMC E5 and EC respectively in single and combinations by solvent evaporation technique with the incorporation of penetration enhancer such as dimethylsulfoxide and dibutyl phthalate as plasticizer In vitro studies concluded that HPMC E5 patches has better release than that of EC patches, which may be attributed to high water vapour permeability of HPMC patches and hydrophobic nature of EC. An attempt was made to incorporate HPMC E5 and EC to the monolithic system for better release and prolong the duration of release. Formulation F7 containing an equal ratio of HPMC E5: EC (5:5) showed maximum and sustained release of 86.816±0.264 within 24 h. Kinetic models were used to confirm the release mechanism of the formulations. Maslinic acid release from the patches F1 to F7 followed non Fickian diffusion rate controlled mechanism.